Arthroscopic Trapeziectomy With 4-mm Arthroscope and Without Traction Tower - Zareen Sui Yin Chiba, M.B.B.S. (HK); Tun Hing Lui, M.B.B.S. (HK), F.R.C.S. (Edin), F.H.K.A.M., F.H.K.C.O.S.; Amanda Mun Yee Slocum, M.B.B.S. (HK), F.R.C.S.Ed. (Orth), F.H.K.A.M., F.H.K.C.O.S. (Arthroscopy Techniques)
Osteoarthritis of the first carpometacarpal joint causes pain and hand function impairment. Pain reduction and preservation or improvement in the thumb motion are the main treatment aims. Surgery is indicated in cases recalcitrant to conservative treatment. Trapeziectomy is the most popular surgical treatment choice. Arthroscopic trapeziectomy is gaining popularity because of its advantage of minimally invasive surgery. Classically, the arthroscopic procedure is performed under continuous traction with a traction tower. Recently, the technique of arthroscopic trapeziectomy without a traction tower has been reported. The purpose of this Technical Note is to describe the details of refining this technique by performing arthroscopic trapeziectomy with a 4-mm arthroscope and without a traction tower. This has the advantage of more effective bone resection.